THE TEREK-CASPIAN FOREDEEP OIL AND GAS CONTENT IN THE TERRITORY OF THE DAGESTAN PLAIN - R. M. Aliev; R. K. Gumarov (Вестник Дагестанского государственного технического университета: Технические науки)
Aim. In article on the basis of the modern data given analysis and previous geological and geophysical information are marked the prospects of subsurface oil and gas content on the territory Dagestan Plain.Methods. A brief history geological development and seismostratigraphic characteristics of the region are presented. Determined is the formation of the potential trap.Results. It is presented the results of AVO-analysis. It was found that the accuracy of the forecast of oil and gas potential on the results of AVO-analysis determined depth of the research object and the nature of its hydrocarbon saturation. The magnitude of the deviation values of AVO-analysis parameters can predict gas and oil and gas saturation.Conclusion. The proposed strategy of «analogue» development Dagestan sector of the Caspian sea shelf.